Pengawasan Mal Administrasi oleh Ombudsman Aceh terhadap Pelayanan Publik atau Pelayanan Kemasyarakatan pada BPBD Bireuen - Yusuf Adan , Hasanuddin; Zubaidi, Zaiyad; Muhammad Iqbal Rahman (STAINI Press, 2022)
The implementation of a clean and effective government aspired to by the community, public services and law enforcement are two inseparable aspects of efforts to create a democratic government that aims to improve people's welfare, justice, legal certainty, clean and transparent government (clean government and good governance). governance). In fact, there are still many maladministration carried out by public services. The formulation of the problem in this research is how is the Islamic perspective related to supervision and how is the process of public supervision and what factors are the obstacles experienced by the Aceh Ombudsman. This type of research is classified as field research, which is descriptive in nature, namely research that describes and describes data sourced from primary data through interviews, observations and reports in the form of documents and secondary data by conducting library research in the form of Al- Qur'an, Hadith, opinions of scholars, laws and regulations, documents and books and other scientific works. Based on the results of the study, it can be concluded that there is maladministration in Bireuen Regency regarding the misuse of public service facilities in the field of BPBD damkar, so that the Ombudsman conducts an investigation of the service. Fiqh Siyasah's review of the supervision carried out by the Ombudsman does not conflict with the Shari'a, but the supervised service is not responsible for its service to the needs of the community.